(untitled) (Revista Electrónica Calidad en la Educación Superior, 2018)
The present text systematizes the research experience in the Chair of Statistics and Educational Administration, the Career in Educational Administration, with the subject Administration of Education in the subject of evaluation of learning, from a methodological approach to evaluate to learn. The aspects that give origin to the research process are addressed, the theoretical bases that sustain and support the analysis linked to the theoretical-methodological approach of evaluating to learn. In addition, the stages developed and the challenges to achieve improvements in the selected subject are described, all from a critical perspective.